HUBUNGAN ANTARA KINERJA PEMBANGUNAN EKONOMI DENGAN PENGANGGURAN TERDIDIK DI PROVINSI JAWA TENGAH TAHUN 2005-2010 - , BENEDICTA ANIN P L, Dr. Sukamdi, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
High educated unemployment is one of the important issues in economic development in Central Java Province. Increased rate of economic growth in Central Java Province have not been able to reduce the number of educated unemployed. This condition is contrary to Okun's law which states that the number of unemployed in a country is inversely proportional to the rate of economic growth. The question is whether the indicators that can be used as an explanatory variable to the educated unemployed. This study aimed to (a) determine the performance of economic development in Central Java Province based indicators the rate of economic growth, the Gini index, and the employment structure transformation industrial sector, (b) analyze the spatial pattern, and (c) determine the relationship between the economic development performance with numbers educated unemployment in 2005-2010. The analysis technique used is the analysis of spatial, temporal, and descriptive. Results of this study showed that the majority of districts in Central Java Province during 2005-2009 have a low the rate of ecnomic growth. Meanwhile, the Gini index in Central Java Province from year 2006-2009 has not been evenly distributed. On the other hand, only a minority district / town in Central Java Province during the period 2005-2009 which has undergone structural transformation of employment from agriculture to industry. Another interesting result was that there was no relationship between the rates of ecnomic growth with educated unemployment. Similarly, there was no relationship between Gini index and educated unemployment. However, the transformation of the structure of the industrial sector employment is negatively related to the number of educated unemployment. It means that the educated unemployed in the Central Java Province is more closely related to the transformation of the structure of industrial sector employment